Exercise training normalizes impaired NOS-dependent responses of cerebral arterioles in type 1 diabetic rats - Mayhan, William G. (American Physiological Society, 2011)
Our goal was to examine whether exercise training (ExT) could normalize impaired nitric oxide synthase (NOS)-dependent dilation of cerebral (pial) arterioles during type 1 diabetes (T1D). We measured the in vivo diameter of pial arterioles in sedentary and exercised nondiabetic and diabetic rats in response to an endothelial NOS (eNOS)-dependent (ADP), an neuronal NOS (nNOS)-dependent [N-methyl-d-aspartate (NMDA)], and a NOS-independent (nitroglycerin) agonist. In addition, we measured superoxide anion levels in brain tissue under basal conditions in sedentary and exercised nondiabetic and diabetic rats. Furthermore, we used Western blot analysis to determine eNOS and nNOS protein levels in cerebral vessels/brain tissue in sedentary and exercised nondiabetic and diabetic rats. We found that ADP and NMDA produced a dilation of pial arterioles that was similar in sedentary and exercised nondiabetic rats. In contrast, ADP and NMDA produced only minimal vasodilation in sedentary diabetic rats. ExT restored impaired ADP- and NMDA-induced vasodilation observed in diabetic rats to that observed in nondiabetics. Nitroglycerin produced a dilation of pial arterioles that was similar in sedentary and exercised nondiabetic and diabetic rats. Superoxide levels in cortex tissue were similar in sedentary and exercised nondiabetic rats, were increased in sedentary diabetic rats, and were normalized by ExT in diabetic rats. Finally, we found that eNOS protein was increased in diabetic rats and further increased by ExT and that nNOS protein was not influenced by T1D but was increased by ExT. We conclude that ExT can alleviate impaired eNOS- and nNOS-dependent responses of pial arterioles during T1D.